Seroprevalence of Hepatitis A and E Virus Infections Among Healthy Population in Shiraz, Southern Iran - Asaei, Sadaf (Jundishapur J Microbiol, 2015)
BACKGROUND: Enterically-transmitted acute viral hepatitis is caused predominantly by hepatitis A virus (HAV) and hepatitis E virus (HEV). The prevalence of HEV and HAV infections varies in different geographical regions. OBJECTIVES: This study was conducted to determine the prevalence of HEV and HAV infections among Iranian healthy individuals in southern Iran. PATIENTS AND METHODS: Totally, 1030 samples were collected from healthy subjects in schools, those referred to tertiary outpatient clinics and health centers in Shiraz between November 2011 and May 2012. Their ages ranged between six months and 95 years. The presence of total anti-HAV and anti-HEV immunoglobulin M (IgM) in plasma was assessed by ELISA. RESULTS: The results showed that 66.2% and 0.6% of the general population in this area were positive for total anti-HAV and IgM antibodies by ELISA, respectively. As seen, 13.4% and 0.9% were positive for total anti-HEV and IgM antibodies, respectively. The difference in total anti-HAV and anti-HEV antibodies was significant among the age groups (P < 0.001). CONCLUSIONS: This study showed that the prevalence rates of HAV and HEV antibodies were positively correlated with age. The results demonstrated that the infection with these two viruses in the region was high and some high-risk individuals including females at child-bearing age were more susceptible. HAV vaccination could be recommended for antibody-negative adults.